The effectiveness of a multidisciplinary intervention strategy for the treatment of symptomatic joint hypermobility in childhood: a randomised, single Centre parallel group trial (The Bendy Study) - Peter Bale; Vicky Easton; Holly Bacon; Emma Jerman; Laura Watts; Garry Barton; Allan Clark; Kate Armon; Alex J. MacGregor (Pediatric Rheumatology Online Journal, 2019)
Abstract Introduction Joint hypermobility is common in childhood and can be associated with musculoskeletal pain and dysfunction. Current management is delivered by a multidisciplinary team, but evidence of effectiveness is limited. This clinical trial aimed to determine whether a structured multidisciplinary, multisite intervention resulted in improved clinical outcomes compared with standard care. Method A prospective randomised, single centre parallel group trial comparing an 8-week individualised multidisciplinary intervention programme (bespoke physiotherapy and occupational therapy in the clinical, home and school environment) with current standard management (advice, information and therapy referral if deemed necessary). The primary endpoint of the study was between group difference in child reported pain from baseline to 12 months as assessed using the Wong Baker faces pain scale. Secondary endpoints were parent reported pain (100 mm visual analogue scale), parent reported function (child health assessment questionnaire), child reported quality of life (child health utility 9-dimensional assessment), coordination (movement assessment battery for children version 2) and grip strength (handheld dynamometer). Results 119 children aged 5 to 16 years, with symptomatic hypermobility were randomised to receive an individualised multidisciplinary intervention (I) (n = 59) or standard management (S) (n = 60). Of these, 105 completed follow up at 12 months. No additional significant benefit could be shown from the intervention compared to standard management. However, there was a statistically significant improvement in child and parent reported pain, coordination and grip strength in both groups. The response was independent of the degree of hypermobility. Conclusion This is the first randomised controlled trial to compare a structured multidisciplinary, multisite intervention with standard care in symptomatic childhood hypermobility. For the majority, the provision of education and positive interventions aimed at promoting healthy exercise and self-management was associated with significant benefit without the need for more complex interventions. Trial registration The trial was registered prospectively with the national database at the Clinical Research Network (UKCRN Portfolio 9366). The trial was registered retrospectively with ISRCTN (ISRCTN86573140).